FITOKIMIA, DAN AKTIFITAS ANTIBAKTERI DARI Etlingera sublimata Poulsen (ZINGIBERACEAE), TUMBUHAN ENDEMIK SULAWESI: Phytochemical and Antibacterial Activity of Etlingera sublimata Poulsen (Zingiberaceae), Endemic Plant to Sulawesi - Ramadanil Pitopang; Endang Lestari; PUTI ANDALUSIA SARIGANDO Banilai; Wahyu Harso (Biocelebes, 2022)
The research entitled "Phytochemical Screening and antibacterial activity of Etlingera sublimata Poulsen (Zingiberaceae), an Endemic Sulawesi of Plants was conducted from January 2020 to June 2020, at the Plant Biosystematics Laboratory and Biotechnology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Tadulako University. Samples of E. sublimata were collected from the mountane forests of the Lore Lindu National Park (LLNP), arround Sedoa village, Lore Utara District, Poso Regency The objectives of the research were to analyze the secondary metabolite compounds in E. sublimata plants and to determine the antibacterial activity of E. sublimata leaves extract in againts Salmonella thypii bacteria. Plant samples were extracted by maceration methods with 96% ethanol as a solvent. Actibacterial activity was tested by using agar well diffusion methods. The experiment was designed by Completely Randomized Design (CRD) with seven different concentration of E. sublimata extract (15, 25, 50, 75 and 85%). Extract and standard drugs were prepared in double-distilated water using Nutrient Agar tubes. 2% Chloramphenicol as standard drugs was used as a positive control and sterile aquadest was used as a negative control. The inhibition zone of bacteria and yeast growth around the disk was measured after 18 to 24 h incubation at 37°C. The results showed that the stem contains alkaloids, flavonoids, terpenoids, tannins and saponins. The rhizome containts alkaloid, flavonoids, terpenoids, tannins and saponins, the flowers containts alkaloid, terpenoids and tannins, while the leaves containts tannin and saponin compounds. Leaves extract of E.sublimata has inhibition activity on the cell growth a pathogenic Salmonella thypi bacteria that the effective extract concentration was 50% with an average inhibition zone ​​2.67 mm.